Mastering Innovations in the Lens of Information and Communications Technology (ICT) Competence and Practices of 21st Century Filipino Teachers: A Comparison among Thailand, Vietnam, and the Philippines - Hero, Jesson L.; Zulueta, Ma. Cristina E.; Gloria, Daianne S.; Tongol, Jose Carlo L.; Cruz, Aaron C. Dela; Sagun, Sr. Angelita T.; Cajurao, Fr. Gil V.; EdD, Wendell C. Cabrera, (Future Science / FSH-PH Publications, 2021)
In the advent of Information and Communications Technology in education, competence and skills for technology-based instruction are essential for teachers. With this, there is a need to continually train and equip teachers with understanding and capabilities that will enable them to maximize the utilization of ICT in their instructional practices. Hence, this research determined the correlation of teachers' level of ICT competence towards their ICT integration practices and corroborated it to existing findings in Thailand and Vietnam. Using a descriptive-correlational design, the researchers found a link between and among variables. The chosen respondents for the study consisted of one-hundred and nineteen (119) teachers from private institutions in a district in Bulacan. Results showed that teachers exhibited competence towards ICT integration. More so, teachers highly practiced ICT integration as part of their instructional practices and strategies in teaching. Results of regression analysis of the data revealed that the six dimensions of ICT competence significantly correlated to the teachers' ICT integration practices. The pedagogical practices and competence of Filipino teachers are the same as the Thai and Vietnamese teachers towards ICT Integration. It is recommended that schools maintain teachers' competence and confidence towards ICT integration thru enhancement or faculty development programs.